Mitigating Production Risk in Aloe Vera Farming on Peatlands: An Analysis of Input Factors in North Pontianak, Indonesia - Riyansah, Riki; Kurniati, Dewi; Imelda, Imelda (Jambura Agribusiness Journal, 2025)
Indonesia has extensive peatland areas that play an important role in national agricultural production. Still, farming on peat soils is often constrained by high production risks caused by low soil fertility, acidity, and unstable structure. Aloe vera is one of the leading horticultural commodities in Pontianak and has high economic value; however, its cultivation on peatlands is increasingly threatened by fluctuating yields and land conversion. This study analyzes the level of production risk in aloe vera farming on peatlands and identifies key factors that influence this risk. Using primary data from 81 farmers selected through saturated sampling, production risk was measured using the Coefficient of Variation (CV). In contrast, factors affecting production and its variability were examined using the Cobb–Douglas production function with the Just Pope approach. Results show that aloe vera farming on peatlands has a low production risk (CV=20.3%). Labor and seedlings significantly increase production, while manure plays a crucial role in reducing production risk. The finding that manure contributes substantially to risk reduction provides practical insights for peatland management and can serve as a key recommendation for improving the sustainability of aloe vera farming in North Pontianak District.